ON PARTICIPATION IN INTERNATIONAL CONVERTIONS ON AIR TRANSPORT: IMPERATIVE NECESSITY OR OPTION - V. G. Afanasiev (Научный вестник МГТУ ГА)
The article describes the problem of participation in aviation conventions on air transport, discuses priorities and responsibilities of participants who have ratified the conventions and obligations of their air companies.